Efficacy and safety of limus-eluting versus paclitaxel-eluting coronary artery stents in patients with diabetes mellitus: A meta-analysis. (1st April 2015) - Liu, Yuqi; Gao, Lei; Song, Yanqiu; Chen, Lian; Xue, Qiao; Tian, Jinwen; Wang, Yu; Chen, Yundai
Abstract: Background/objectives: The relative efficacy and safety of limus-eluting stent (LES) versus paclitaxel-eluting stent (PES) in DM patients remain unclear. Methods: The PubMed, EMBASE, and Cochrane Central Register of Controlled Trials electronic databases were searched from January 2001 to December 2013. Clinical trials that performed head-to-head comparisons of LES versus PES implantation in patients with DM were considered for inclusion. Results: This meta-analysis included 28 clinical trials involving 23, 678 patients: 9953 who underwent sirolimus-eluting stent (SES) implantation, 4209 underwent everolimus-eluting stent (EES) or zotarolimus-eluting stent (ZES) implantation, and 9516 underwent PES implantation. The short-term target lesion revascularization (TLR) rate was significantly lower after SES implantation than after PES implantation (3.6% vs 6.3%; odds ratio (OR): 0.659; P  = 0.014), but there were no significant differences in the rates of target vessel revascularization (TVR), stent thrombosis (ST), myocardial infarction (MI), all-cause mortality, or major adverse cardiac events (MACE). There were no differences in the longer-term rates of TLR, TVR, ST, MI, all-cause mortality, or MACE between SES versus PES. Second-generation LES (EES or ZES) implantation resulted in lower rates of ST (2.1% vs 3.3%; OR: 0.586; P  < 0.001), MI (2.3% vs 4.1%; OR: 0.527; P  = 0.001), and MACE (8.0% vs 10.3%; OR: 0.796; P  = 0.007) than PES implantation. Conclusions: In patients with DM, short- and longer-term MACE rates were similar after first-generation LES and PES implantation. The second-generation LES may be better than PES implantation in rates of ST, MI, and MACE. Highlights: The relative efficacy and safety of limus-eluting stent (LES) versus paclitaxel-eluting stent (PES) in DM patients remain unclear. This meta-analysis in cluded 28 clinical trials involving 23, 678 patients: 9953 who underwent sirolimus-eluting stent (SES) implantation, 4209 underwent everolimus-eluting stent (EES) or zotarolimus-eluting stent (ZES) implantation, and 9516 underwent PES implantation. In this article the results showed short- and longer-term MACE rates were similar after first-generation LES and PES implantation in patients with DM. The second-generation LES may be better than PES implantation in rates of ST, MI, and MACE.